Preparation of Arabic Teachers at IPG Kpi Malaysia: Community Service Using the Addie Approach - Asep Sopian; Hikmah Maulani; Maman Abdurrahman; Syihabuddin; Shofa Musthofa Khalid; Nalahuddin Saleh; Tatang; Muhammad Faris Imaduddin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This community service aims to analyze the preparation and training of Arabic teachers in Indonesia and Malaysia. The research uses a descriptive qualitative approach to present objective and scientific empirical facts. The data sources used in this study include secondary data from references and research objects related to Arabic language education in both countries. The analysis results indicate that in Indonesia, the preparation of Arabic teachers is more flexible with more open regulations and opportunities. Conversely, in Malaysia, the preparation and training of Arabic teachers are more stringent with specific qualifications that must be met. The study also finds that using technology and resources in teacher training in Malaysia is more structured through the ADDIE instructional design model, which is considered effective in enhancing educational quality. The findings emphasize the importance of improving the professionalism of Arabic teachers through structured and continuous training in both countries.